KONTRIBUSI PENDAPATAN USAHATANI PADI SAWAH TERHADAP PENDAPATAN KELUARGA PETANI DI DESA RASI KECAMATAN RATAHAN (Contribution of Rice Business Income to Farmer Families Income In Rasi Village, Ratahan Sub District) - Nela Susana Soputan; Celcius Talumingan; Gene H. M. Kapantow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to analyze the contribution of lowland rice farming income to family income of farmers in Rasi Village, Ratahan District. This research was conducted in Rasi Village, Ratahan District, Southeast Minahasa Regency for three months, from November 2019 to January 2020, starting from preparation, data collection, to the preparation of research reports. The data obtained were analyzed descriptively and quantitatively and will be presented in tabular form. The research results showed that lowland rice farming contributed to the income of family farmers in Rasi Village, Ratahan District with a percentage yield of 35.02% in 0.1-0.25 ha of land, 51.90% in 0.26-0.50 ha of land, and 52.55% in >0.51 ha of land. This means that lowland rice farming in Rasi Village can be a source of income for farmers to meet the needs of farmer families.Keywords: Contribution, Income, Farmer, Rice Farming